Analysis of buildings' energy consumption by means of exergy method. (21st October 2008) - Tronchin, Lamberto; Fabbri, Kristian
Among the objectives of the Directive 2002/91/EC and of the Council "Energy performance of buildings", Energy Performance of Building Directive (EPBD) the energy certification of buildings represents a fundamental role. The method here described starts from the LowEX tool, previously developed in the IEA ECBCS Annex 37 framework. By using the exergy approach, new (non-economic) indices could be utilised, as Tonne of Oil Equivalent (TOE), CO2 emission, or not-renewable energy uses. The ratio between TOE produced by the boiler and the exergy used by the system represents the exergy parameter.